The impact of Ground oil Fields on the human resources - Alsadon, Raad (Iraqi Journal of Science, 2024)
This research includes the study of the harsh environment areas in which engineers and workers operate in drilling oil wells, and their own characteristics in terms of nature and the climate and other surrounding factors, that negatively large amount affect on all the staff, present in comparison with other lands, so the study showed the preparations administrative and methodology that must be taken to confront the problems that may arise or for the purpose of avoiding. One of these things should be addressed is the process of adaptation of the staff live in the remote desert land and under difficult living conditions. The study also demonstrated all kinds of diseases and ill health which afflict the staff due to climatic conditions that accompany their daily business and physical stress and intellectual effort. The study explains methods of preventing and treating diseases that occur in such areas simultaneously and rapidly in order not to influence the morale of other workers. The study showed the standard amounts for drinking water and salts to be allocated for each worker Who are exposed to physical stress while working in the pits and the use of heavy equipments through the practical testing some of the engineers and workers drilling to see the impact of this environment and purpose for obtaining the result and estimated the conclusions.